Which spinal lesions are associated with new bone formation in patients with ankylosing spondylitis treated with anti-TNF agents? A long-term observational study using MRI and conventional radiography. Issue 10 (14th July 2013) - Baraliakos, X; Heldmann, F; Callhoff, J; Listing, J; Appelboom, T; Brandt, J; Van den Bosch, F; Breban, M; Burmester, GR; Dougados, M; Emery, P; Gaston, H; et al.
Abstract : Objective: To study the relationship of spinal inflammation and fatty degeneration (FD) as detected by MRI and new bone formation seen on conventional radiographs (CRs) in ankylosing spondylitis (AS). Methods: CRs at baseline, 2 years and 5 years and spinal MRIs at baseline and 2 years of 73 AS patients treated with infliximab in European AS Infliximab Cohort were available. Relative risks (RR) were calculated with a general linear model after adjustment for within-patient variation. Results: In a total of 1466 vertebral edges (VEs) without baseline syndesmophytes, 61 syndesmophytes developed at 5 years, the majority of which (57.4%) had no corresponding detectable MRI lesions at baseline. VEs with both inflammation and FD at baseline had the highest risk (RR 3.3, p=0.009) for syndesmophyte formation at 5 years, followed by VEs that developed new FD or did not resolve FD at 2 years (RR=2.3, p=0.034), while inflammation at baseline with no FD at 2 years had the lowest risk for syndesmophyte formation at 5 years (RR=0.8). Of the VEs with inflammation at baseline, >70% resolved completely, 28.8% turned into FD after 2 years, but only 1 syndesmophyte developed within 5 years. Conclusions: Parallel occurrence of inflammation and FD at baseline and development of FD without prior inflammation after 2 years were significantly associated with syndesmophyte formation after 5 years of anti-tumour necrosis factor (TNF) therapy. However, the sequence 'inflammation–FD–new bone formation' was rarely observed, an argument against the TNF-brake hypothesis. Whether an early suppression of inflammation leads to a decrease of the risk for new bone formation remains to be demonstrated.